Transport features and structural optimization of solid lipid nanoparticles crossing the intestinal epithelium. Issue 74 (25th July 2016) - Chai, Guihong; Meng, Yufang; Chen, Shaoqing; Hu, Fuqiang; Gan, Yong; Yuan, Hong
Abstract : In vitro simulated intestinal epithelial cell monolayer is a novel avenue to screen optimal SLNs formulations. Abstract : Solid lipid nanoparticles (SLNs) have been used to encapsulate drugs with poor solubility and membrane permeability to improve oral bioavailability. In vitro experiments that determine the SLNs fabrication parameters necessary to achieve satisfactory absorption is important to avoid costly and time-consuming animal experiments. In this study, the Madin–Darby canine kidney (MDCK) cell line was employed to construct a simulated epithelial cell monolayer, and the transport features of SLNs were investigated. Subsequently, SLNs prepared with solid lipid materials with different carbon chain lengths or modified with different amounts of polyethylene glycol monostearate (SA-PEG2000) were used to investigate the relationship between nanoparticle structures and transcytosis efficiency, and the related mechanisms were revealed. Moreover, rats were employed to compare the in vitro and in situ intestinal absorption of these various SLNs. The results demonstrated that the endocytosis and endocellular delivery of SLNs crossing the MDCK cell monolayer were vesicle-mediated processes. Studies of the transport capacity of various SLNs across the cell monolayer showed that the transcytosis of SLNs decreased with increasing carbon chain length, and improved with a certain amount of hydrophilic modification (SA-PEG2000, 20%, w/w). The analysis of molecular mechanisms demonstrated that SLNs prepared by solid lipid materials with a short carbon chain were inclined to be transcytosed via endoplasmic reticulum (ER)- and Golgi complex-mediated pathways; further, SLNs containing an increasingly long carbon chain showed proportionally lower transcytosis by these two organelles. Furthermore, a certain amount of hydrophilic modification can evade transcytosis via the ER- and Golgi complex-mediated pathways for more effective transcytosis. Moreover, the intestinal absorption results were consistent with that found in the simulated epithelial cell monolayer. In conclusion, SLNs prepared with solid lipid materials with a medium-length carbon chain and surface-modified with a certain amount of hydrophilic modification can transcytosis effectively.